Using water - Hewitt, Sally, 1949- (St. Catharines, Ont. ; New York : Crabtree Pub., 2009)
Discusses the importance of water and its conservation, covering how to save it, how it is cleaned and reused, pollution, ice, the melting of the polar caps, and emergencies around the world, and includes a glossary.
Includes bibliographical references (p. 31) and index.
Library Media Connection
Resource Links
Teacher Librarian
5.4
3-6.
Keywords: Water use -- Juvenile literature; Water-supply -- Juvenile literature; Water supply; Water use; Water supply